Participation in the designing of an iPod project, to improve the Oral Reading Fluency of Communication and Internet Studies students, following an English for Specific Purposes course at Cyprus University of Technology Language Centre, in the designing of the tasks and in the creation of the questionnaires. - Georgiadou, Olga (My University, 2026)
Participation in the designing of an iPod project, to improve the Oral Reading Fluency of Communication and Internet Studies students, following an English for Specific Purposes course at Cyprus University of Technology Language Centre, in the designing of the tasks and in the creation of the questionnaires.